A Pink Herring in the Colon: A Case Report of Eosinophilic Colitis Masking Invasive Adenocarcinoma of the Colon - David Malcolm Milne; Jason Rattan; Alyssa Muddeen; Amrit A. Rambhajan (Case Reports in Surgery)
Eosinophilic colitis is an inflammatory condition in which the wall of the colon becomes infiltrated by eosinophils which stain densely pink on microscopy. It is an uncommon clinical entity which has a long list of differential diagnoses. We present a case of a patient whose biopsy at colonoscopy revealed eosinophilic colitis which led to a delay in the diagnosis and subsequent treatment of colon cancer. A 35-year-old male presented with a six-week history of right lower quadrant abdominal pain associated with diarrhoea and weight loss. Colonoscopy showed an inflamed cecum; computed tomography revealed a small ascitic fluid collection in the right iliac fossa. Biopsy showed eosinophilic colitis, and he was treated conservatively with albendazole and mesalamine. The patient failed to improve over the following month with continued weight loss. A repeat CT scan showed a right iliac fossa mass. A right hemicolectomy was performed with histopathology from the specimen showing mucinous adenocarcinoma. Eosinophilic colitis can mask colon cancer and should be considered a diagnosis of exclusion.